The Coffee Business Management with Islamic Symbols: Total Motivation Model and Shari’ah Enterprise Theory Approach - Novi Puspitasari (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
There is a coffee product under the brand BIKLA. This coffee is produced by the Pesantren (Islamic boarding school) cooperative located in Bangsalsari District, Jember Regency. This coffee is unique because on the front packaging it says